Bibliometric and visualized analysis of work engagement in business management - Zhang, Ziqiong; Mohamed, Rosmah; Rahman, Rozanah Ab; Dong, Tao (Business: Theory and Practice, 2025)
Within business management, the growing interest in work engagement stems from its recognised role in mitigating employee well-being, bolstering job satisfaction, and optimising organisational outcomes. This review comprehensively explores the knowledge structure of work engagement in business management, analysing 563 publications from the Scopus database spanning 2005 to 2023 through performance analysis, co-citation analysis, co-authorship analysis, keyword co-occurrence analysis, and content analysis. This review outlines prevailing trends and identifies influential scholars, articles, institutions, and leading countries. It illuminates the current state of scientific collaboration, providing a rationale for developing countries to seek academic cooperation with developed countries. Additionally, it delves into six current themes and four future directions, providing a robust theoretical framework for future research endeavours.